2020
DOI: 10.3847/1538-4357/abb469
|View full text |Cite
|
Sign up to set email alerts
|

ALMA CO Observations of Gamma-Ray Supernova Remnant N132D in the Large Magellanic Cloud: Possible Evidence for Shocked Molecular Clouds Illuminated by Cosmic-Ray Protons

Abstract: N132D is the brightest gamma-ray supernova remnant (SNR) in the Large Magellanic Cloud (LMC). We carried out 12CO(J = 1–0, 3–2) observations toward the SNR using the Atacama Large Millimeter/submillimeter Array (ALMA) and Atacama Submillimeter Telescope Experiment. We find diffuse CO emission not only at the southern edge of the SNR as previously known, but also inside the X-ray shell. We spatially resolved nine molecular clouds using ALMA with an angular resolution of 5″, corresponding to a spatial resolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 97 publications
1
24
0
Order By: Relevance
“…N132D is located near a molecular cloud complex, and it has recently been shown that the SNR is interacting with some of the molecular gas [19]. For the hadronic model, preferred by our analysis, the local gas density has to be high n p 10 cm −3 in order to explain the gamma-ray luminosity of N132D.…”
Section: Possible Interactions With Local Molecular Cloudsmentioning
confidence: 87%
See 3 more Smart Citations
“…N132D is located near a molecular cloud complex, and it has recently been shown that the SNR is interacting with some of the molecular gas [19]. For the hadronic model, preferred by our analysis, the local gas density has to be high n p 10 cm −3 in order to explain the gamma-ray luminosity of N132D.…”
Section: Possible Interactions With Local Molecular Cloudsmentioning
confidence: 87%
“…For the hadronic model, preferred by our analysis, the local gas density has to be high n p 10 cm −3 in order to explain the gamma-ray luminosity of N132D. The analysis of observations of HI and CO line emission by [19] shows that the density requirements are easily met. The HI gas cloud around the SNR has a typical density of n H ≈ 30 cm −3 , implying W p ≈ 1 × 10 50 erg.…”
Section: Possible Interactions With Local Molecular Cloudsmentioning
confidence: 96%
See 2 more Smart Citations
“…Collaboration (2018) showed that within statistical errors, there is no significant difference between the TeV γ -rays and the X-ray synchrotron Fig. 15 CO results toward the five Magellanic SNRs N63A (Sano et al 2019b), N49 (Yamane et al 2018), RX J0046.5−7308 (Sano et al 2019c), N132D (Sano et al 2020a), N103B (Sano et al 2018), and the Magellanic superbubble 30 Doradus C (Yamane et al 2021). The CO observations of the LMC SNRs N63A, N49, N132D, N103B, and the LMC superbubble 30 Doradus C were obtained using ALMA, while the SMC SNR RX J0046.5−7308 was observed using the Atacama Submillimeter Telescope Experiment (ASTE).…”
Section: The Origin Of the γ -Raysmentioning
confidence: 98%